2011
DOI: 10.1159/000329802
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Hepatic Parenchyma in Liver Transplant Tolerance: A Paradigm Revisited

Abstract: Unlike other solid organs, liver transplants are spontaneously accepted in a wide range of animal models. In the clinic, transplanted livers also display privileged immunological properties allowing weaning of immunosuppression therapy in up to 20% of selected patients. To explain this phenomenon, many studies have focused on the role of donor-derived ‘passenger’ leukocytes that are thought to induce antigen-specific tolerance by migrating from the graft into recipient secondary lymphoid tissues. Although conv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 227 publications
0
5
0
Order By: Relevance
“…However, a later study questioned whether the presence of donor-strain passenger leukocytes was linked to rat liver allograft (PVG to DA) tolerance as chimaeric donor livers bearing donor, recipient or third-party leukocytes were accepted long term 159 . The observation of higher levels of apoptosis of graft-infiltrating leukocytes in liver allografts than in renal allografts of the same combination of rat strains suggested an important role for this process in the induction of liver transplant tolerance 160 , whereby donor parenchymal or liver-resident cells induced alloreactive recipient T cell death by neglect [161][162][163] . In a mouse liver transplant model, differential migration of donor passenger leukocytes via the blood to recipient lymph nodes and the spleen within 24 h after transplantation has been described, whereas donor natural killer cells and natural killer T cells remained in the liver and blood 164 .…”
Section: Mechanisms Underlying Tolerancementioning
confidence: 99%
“…However, a later study questioned whether the presence of donor-strain passenger leukocytes was linked to rat liver allograft (PVG to DA) tolerance as chimaeric donor livers bearing donor, recipient or third-party leukocytes were accepted long term 159 . The observation of higher levels of apoptosis of graft-infiltrating leukocytes in liver allografts than in renal allografts of the same combination of rat strains suggested an important role for this process in the induction of liver transplant tolerance 160 , whereby donor parenchymal or liver-resident cells induced alloreactive recipient T cell death by neglect [161][162][163] . In a mouse liver transplant model, differential migration of donor passenger leukocytes via the blood to recipient lymph nodes and the spleen within 24 h after transplantation has been described, whereas donor natural killer cells and natural killer T cells remained in the liver and blood 164 .…”
Section: Mechanisms Underlying Tolerancementioning
confidence: 99%
“…Traditional explanations for the muting of T-cell responses within the liver include a bias of liver antigen-presenting cells toward eliciting regulatory, rather than effector, responses, the predisposition of activated T cells toward exhaustion and/or apoptosis attributed to the expression of negative costimulatory molecules and anti-inflammatory cytokines (IL-10 and transforming growth factor beta) by multiple intrahepatic cell populations, the production of soluble MHC class I, and the reduced expression of MHC class II. (49,50) Other possible explanations include the scarcity of IgG3 DSA subclass, activation of liver protective mechanisms (e.g., increasing the number of Kupffer cells to phagocytize the products of DSA reactions), or up-regulation of complement regulatory or cytoprotective molecules on the endothelium. Our observations suggest that some or all of these mechanisms explain the failure of the immune response to cause clinical or histopathological damage to operationally tolerant allografts.…”
Section: Feng Et Al Hepatology February 2017mentioning
confidence: 99%
“…The spleen is sometimes considered more tolerogenic, although most studies have not distinguished the contributions of these organs. Studies using donor livers reconstituted with PLs from the recipient strain have also shown that instead of PLs, the liver parenchyma and/or liver‐resident cells are key determinants of graft outcomes . The liver parenchyma has been suggested to play an important role in tolerance by secreting soluble donor major histocompatibility complex (MHC) class I molecules or by inducing the abortive activation of graft‐reactive T cells …”
mentioning
confidence: 99%